A mouthpart transcriptome for Spodoptera frugiperda adults: identification of candidate chemoreceptors and investigation of expression patterns - Dong, Jun-Feng; Hu, Zhen-Jie; Dong, Bing-Xin; Tian, Cai-Hong (Frontiers in Physiology, 2023)
Moth mouthparts, consisting of labial palps and proboscis, not only are the feeding device but also are chemosensory organs for the detection of chemical signals from surrounding environment. Up to now, the chemosensory systems in the mouthpart of moths are largely unknown. Here, we performed systematic analyses of the mouthpart transcriptome of adult Spodoptera frugiperda (Lepidoptera: Noctuidae), a notorious pest that spreads worldwide. A total of 48 chemoreceptors, including 29 odorant receptors (ORs), 9 gustatory receptors (GRs), and 10 ionotropic receptors (IRs), were annotated. Further phylogenetic analyses with these genes and homologs from other insect species determined that specific genes, including ORco, carbon dioxide receptors, pheromone receptor, IR co-receptors, and sugar receptors, were transcribed in the mouthpart of S. frugiperda adults. Subsequently, expression profiling in different chemosensory tissues demonstrated that the annotated ORs and IRs were mainly expressed in S. frugiperda antennae, but one IR was also highly expressed in the mouthparts. In comparison, SfruGRs were mainly expressed in the mouthparts, but three GRs were also highly expressed in the antennae or the legs. Further comparison of the mouthpart-biased chemoreceptors using RT-qPCR revealed that the expression of these genes varied significantly between labial palps and proboscises. This study provides the first large-scale description of chemoreceptors in the mouthpart of adult S. frugiperda and provides a foundation for further functional studies of chemoreceptors in the mouthpart of S. frugiperda as well as of other moth species.